The Study of the Impact of Obstacle on the Efficiency of Evacuation under Different Competitive Conditions. (2018) - Wang, Guo-yuan; Wu, Fan-yu; Si, You-liang; Zeng, Qin; Lin, Peng
Abstract: A series of experiments were conducted to study the effect of obstacle on the evacuation efficiency of mice under different competitive condition. Firstly, experiments were conducted under low competitive condition. The mice were drove to escape in two typical settings. Setting I is an area of 1.5m wide and 1.5m long and Setting II is a laterally constrained area. For both conditions, tests with and without the obstacle were conducted to study the impact of obstacle on the efficiency of evacuation. At setting I, the average escape time is 305s and 298s respectively for non-obstacle condition and obstacle condition. At setting II, the average escape time is 313s and 298s respectively for non-obstacle condition and obstacle condition. Under low competitive condition, the presence of obstacle has little effect on the evacuation efficiency for both settings. Secondly, experiments were conducted in the same two setting with and without the obstacle under high competitive condition. At setting I, the average escape time is 334s and 297s respectively for non-obstacle condition and obstacle condition. At setting II, the mean escape time is 297s and 328s respectively for non-obstacle condition and obstacle condition. Under high competitive condition, the presence of obstacle reduces the escape time by 11.1% at setting I, whilst it increases the escape time by 10.4% at setting II. The force of mice on the wall close to the exit is recorded to study of impact of obstacle on the pressure.